POLITICAL DEICISION IN THE SPECTRUM OF MODERN POLITICAL GOVERNANCE MODELS - Вінникова, Н.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
This article is an attempt to identify the characteristics of the formation and implementation of political decisions in the light of current models of political governance, namely, the concept of New Public Management, theories of Political Networks, conceptions of Good Governance and Multi-Level Governance. We propose a logistic scheme of comparative analysis of the procedural stages of creating political decisions.